Palladium catalysed aryl enol ether synthesis from vinyl triflates. - Willis, M; Taylor, D; Gillmore, A (2003)
Vinyl triflates can be efficiently converted into the corresponding aryl enol ethers by treatment with a phenol, NaO(t)Bu and a catalyst generated from Pd2dba3 and 2-(di-(t)Bu-phosphino)biphenyl.